Influence of Crystal Growth Conditions on Formation of Macroscopic Inclusions inside Thiourea Crystals. Issue 8 (26th February 2018) - Yan, Shaofeng; Xie, Chuang; Zhang, Xia; Zhou, Ling; Hou, Baohong; Huang, Jiting; Zhou, Lina; Yin, Qiuxiang
Abstract: Macroscopic inclusion is an influential defect which affects purity of crystals during crystallization and remains not fully understood. In this work, we chose thiourea as the model material to investigate inclusion formation in detail. Recrystallization of thiourea were performed in deionized water, ethylene glycol, methanol, ethanol, n‐propanol, and n‐butanol under various temperature and supersaturation via cooling or evaporative modes. A series of plate‐like inclusions could form and be parallel to specific crystal faces. Polar solvent was found to be promotive to the inclusion formation due to the enhancing solute‐solvent interaction. The effect of supersaturation on inclusion formation was found to be complicated. A supersaturation window was found in which increasing supersaturation can stimulate forming inclusions. Under the lower threshold of the window, inclusion can seldom form due to low crystal growth. Beyond the upper threshold, however, inclusion formation also decreased. This supersaturation effect was explained using the "hunger center" mechanism in which the growth rate difference between the corners/edges and the center part of crystal face was considered. Moreover, a 4‐stage process during inclusion formation in batch crystallization was also discussed. Abstract : The supersaturation generally stimulates the inclusion formation. But there exists a supersaturation threshold above which inclusions can seldom form (see figure). The formation of macroscopic inclusions and the supersaturation effect on inclusion formation were interpreted with the "hunger center" mechanism.